Evaluasi kinerja keuangan bank mega syariah : analisis net operating margin periode 2019 - 2024 - Mukti, Fitri Ana (Maliki Interdisciplinary Journal, 2026)
This study aims to evaluate the financial performance of Bank Mega Syariah through an analysis of the Net Operating Margin (NOM) during the period 2019–2024. NOM serves as a key indicator for assessing the bank’s operational efficiency in generating net operating income relative to its productive assets. The results reveal significant fluctuations over the six-year period. In 2019–2020, NOM remained at a low level, reflecting high operational expenses and the impact of economic instability during the early phase of the COVID-19 pandemic. The years 2021–2022 marked a substantial increase, with NOM surpassing 5%, indicating effective financing strategies, stronger operational income, and improved cost efficiency during the economic recovery phase. However, a decline occurred in 2023–2024, suggesting pressure on operating income and challenges in maintaining productive asset quality. Overall, the findings highlight the need for Bank Mega Syariah to strengthen operational efficiency strategies to ensure sustainable financial performance in the future.